KEPEMIMPINAN KEPALA DESA DALAM PEMBANGUNAN DI DESA ONGKOL PADANG KECAMATAN MENYUKE KABUPATEN LANDAK - Maksima E.01108087, Meliana (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
This thesis aims to suggest the Leadership of the headman in Developing Ongkol Padang Village, District of Menyuke, Landak Regency. This thesis was carried out because the leadership of the headman of Ongkol Padang Village is not optimal compared to the leadership in other villages. This study uses qualitative descriptive research. This research had two phases: First phase was finding out leadership problems; and the second was defining leadership problems, making alternative leadership, and giving recommendation or suggestion. The research conducted in Village of Ongkol Padang, DistrictÂ  of Menyuke, Landak Regency. The subjects of the research were the headman of the village, and his staff in the village head office, community leaders, and the people in the village. The research finding shows that the leadership of the headman in developing his village, including the service given is not optimal because of imbalance responsibilities, positive role and bad communication. Therefore, it is suggested that the headman should improve his responsibilities, roles and communication to his people.Â Keyword: Leadership, Headman, Village Development.Â